2018
DOI: 10.14203/j.mev.2018.v9.57-64
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency improvement of photovolatic by using maximum power point tracking based on a new fuzzy logic controller

Abstract: Maximum power point tracking (MPPT) is a technique to maximize the power output of photovoltaic (PV). Therefore, to achieve higher PV efficiency, the development of MPPT control algorithm is necessary. Recently, it was revealed that fuzzy logic controller (FLC) is better than other control algorithms and is possible toe developed. This study fabricated and implemented MPPT based on the proposed a new FLC. Input Calculator (IC) via sensors reads current and voltage of PV and generates the comparison of voltage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…As a result, the PV systems' energy yield was drastically reduced. The various MPPT algorithms are discussed in this study along with their benefits and drawbacks for uniform insolation and partial shading circumstances [19][20][21][22][23][24][25][26]. Effendy et al [21] concluded that the MPPT based on a new FLC can increase the overall efficiency of the system to 3%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the PV systems' energy yield was drastically reduced. The various MPPT algorithms are discussed in this study along with their benefits and drawbacks for uniform insolation and partial shading circumstances [19][20][21][22][23][24][25][26]. Effendy et al [21] concluded that the MPPT based on a new FLC can increase the overall efficiency of the system to 3%.…”
Section: Introductionmentioning
confidence: 99%
“…The various MPPT algorithms are discussed in this study along with their benefits and drawbacks for uniform insolation and partial shading circumstances [19][20][21][22][23][24][25][26]. Effendy et al [21] concluded that the MPPT based on a new FLC can increase the overall efficiency of the system to 3%. The proposed FLC system has a robust performance under mode changing while input wind speed changes and the modified technique was found to be highly reliable and suitable for different complex practical applications [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…A number of previous studies discussed how each section could be improved. For example, increasing the power production [9][10], intensifying storage unit [11] [12][13], optimizing transmission line [14][15] [16], and improving distribution network [17][18] [19].…”
Section: Introductionmentioning
confidence: 99%